Localization of magnon modes in a curved magnetic nanowire: Современные проблемы нелинейной физики магнетизма. I. Динамические солитоны - Gaididei, Yuri; Kravchuk, Volodymyr P.; Mertens, Franz G.; Pylypovskyi, Oleksandr V.; Saxena, Avadh; Sheka, Denis D.; Volkov, Oleksii M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2018)
Spin waves in magnetic nanowires can be bound by a local bending of the wire. The eigenfrequency of a truly local magnon mode is determined by the curvature: a general analytical expression is established for any infinitesimally weak localized curvature of the wire. The interaction of the local mode with spin waves, propagating through the bend, results in scattering features, which is well confirmed by spin-lattice simulations.